English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-10-27 14:32:22 · 7 answers · asked by Ak B 1 in Science & Mathematics Mathematics

7 answers

4x + y - 12x^2 -3xy =
4x+y - 3x(4x+y) =
(4x+y)(1-3x)

2006-10-27 16:16:50 · answer #1 · answered by Anonymous · 0 0

set the equation equal to zero
4x + y - 12x^2 - 3xy =0
group together each side and find common factor
(4x + y) - 3x(4x - y) =0
separate again
(1 - 3x)(4x - y)
solve each set of parentheses by setting equal to zero
1-3x=0 4x-y=0
-3x=-1 -y=-4x
X=1/3 y=4x
y=4/3

2006-10-27 14:47:31 · answer #2 · answered by toeknuckle23 1 · 2 0

4x+y-12x.x-3xy stays the same

2006-10-27 19:59:05 · answer #3 · answered by yo-yo 3 · 0 0

4x + y - 12x^2 - 3xy =
(4x + y) - 3x(4x - y) =
(1 - 3x)(4x - y)

2006-10-27 14:38:18 · answer #4 · answered by Helmut 7 · 0 0

4x+y-12x^2-3xy=1(4x+y)-3x(4x+y)
=(4x+y)(1-3x)

2006-10-28 02:57:52 · answer #5 · answered by chill 2 · 0 0

it is easy
the answer is 4x+y-12x(square)-3xy=(1-3x)(4x+y)

2006-10-27 16:32:56 · answer #6 · answered by peterwan1982 2 · 0 1

There are no terms to combine in this expression. What is your question?

2006-10-27 14:39:41 · answer #7 · answered by Anton 3 · 0 1

fedest.com, questions and answers